Conductivity and Permittivity of Irradiated Rats’ Kidney Tissue - الشريف عالية محمد; الحاج أحمد محمد; المرغني خالد عبد الحفيظ; الحماصي أحمد إمحمد (The Libyan Journal of Science, 2020)
It is important to understand the respond and behavior of tissues to bioelectric properties, after their exposure to radiation. The knowledge of these properties is useful to determine the degree of damage, and therefore, help in medical diagnosis that leads to effective therapy. In this paper, the conductivity, relative permittivity and radiation effects on rat’s kidney tissue is studied over a frequency range from 300 Hz to 5 MHz. The studied objects were exposed to an x-ray which provided a dose of (0.5 – 6 Gy). This was carried over a different time period extend from 2 days to 30 days. The results showed that the conductivity due to irradiation increases in the second and fourth day. Then, it dropped to the value of the non-irradiated tissue in the sixteenth day and once more showed some increase after 30 days. Furthermore, the conductivity showed increase in value as a function of dose rate. The difference in conductivity reached 0.0429 S/m at a dose of 6 Gy with respect to non-irradiated tissue. However, the relative permittivity did not show any major fluctuations as a function of dose and time variation. The effect of radiation on kidney’s tissue does not show a consistent change during different time after irradiation. Also, the damage on the external cells of tissue does not occur at low radiation ( < 6 Gy) which is in agreement with other studies [18,19,20].